Skeletal muscle metabolism in individuals with spinal cord injury - McCully, Kevin K. (American Physiological Society, 2011)
With increasing survival rates in people with spinal cord injuries (SCI), detection and prevention of metabolic and cardiovascular disease have become increasingly important. Few studies have evaluated in vivo mitochondrial function in paralyzed skeletal muscle. The purpose of this study was to compare oxidative muscle metabolism using the rate of phosphocreatine (PCr) resynthesis measured by magnetic resonance spectroscopy (MRS) in people with SCI and able-bodied (AB) controls. Eight subjects with complete SCI (American Spinal Injury Association Impairment Scale A, levels T3–T12, injury duration 2–13 years) were compared with 12 AB controls. T1-weighted (1)H MR images of the thigh were taken to identify skeletal muscle. Phosphorous MRS was performed with a 13 × 13-cm(2) surface coil placed on the right vastus lateralis in a 3 Tesla clinical MRI scanner. PCr resynthesis was measured after electrical stimulation for 60 s at 4 Hz in SCI and AB and in AB subjects after 39 s of voluntary isometric contractions. Resting metabolites were not different between SCI and AB, except for an elevated phosphodiester peak. PCr recovery was slower in AB subjects using electrical stimulation compared with voluntary exercise (28.4 ± 6.1 vs. 41.5 ± 4.3 s; P < 0.05). PCr recovery rates and calculated muscle maximum oxidative capacity in SCI were both 52% of electrically stimulated AB (P < 0.001). In vivo oxidative metabolism was reduced in paralyzed muscle to a similar extent as seen in people with mitochondrial myopathies and heart failure.